Morphological studies of apoptotic HeLa cells death induced by eurycomanone - Nurkhasanah .; Azimahtol Hawariah Lope Pihie; Jalifah Latip (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2009)
Eurycomanone is a cytotoxic ingredient found in Eurycoma longifolia Jack. Previous studies have noted its activity against many epithelial cell lines. In this study, eurycomanone had obvious cytotoxic effect on HeLa cells by methylene blue staining assays. After HeLa cells were treated with eurycomanone, typical morphological changes, including cytoplasm shrinkage and decrease of cell volume were observed by light microscope. Chromatin condensation and nuclear fragmentation could be observed by fluorescence microscope after staining with Hoechst 33258 nuclear staining. DNA fragmentation and apoptotic body formation that is characteristic of apoptosis could be determined after treated cells were assayed with TUNEL (terminal deoxynucleotidyl transferase mediated d-UTP nick end labeling). The externalization of phosphatidyl serine (PS) could be determined by flow cytometry analysis using Annexin-V/PI double staining. The result suggested that eurycomanone exerted antiproliferative activity on HeLa cells by inducing apoptosis.Key words : eurycomanone, cytotoxic, apoptosis, HeLa